Antimalarial drug sulfadoxine induces gametocytogenesis in Plasmodium berghei - Wihda Aisarul Azmi; Andita Fitri Mutiara Rizki; Achmad Shidiq; Yenny Djuardi; I Made Artika; Josephine Elizabeth Siregar (Malaria Journal, 2024)
Abstract Background The spread of antimalarial drug resistance parasites is a major obstacle in eliminating malaria in endemic areas. This increases the urgency for developing novel antimalarial drugs with improved profiles to eliminate both sensitive and resistant parasites in populations. The invention of the drug candidates needs a model for sensitive and resistant parasites on a laboratory scale. Methods Repeated Incomplete Treatment (RIcT) method was followed in raising the rodent malaria parasite, Plasmodium berghei, resistant to sulfadoxine. Plasmodium berghei were exposed to an adequate therapeutic dose of sulfadoxine without finishing the treatment to let the parasite recover. Cycles of drug treatment and parasite recovery were repeated until phenotypic resistance appeared. Results After undergoing 3–4 cycles, phenotypic resistance was not yet found in mice treated with sulfadoxine. Nevertheless, the molecular biology of dhps gene (the target of sulfadoxine) was analyzed at the end of the RIcT cycle. There was no mutations found in the gene target. Interestingly, the appearance of gametocytes at the end of every cycle of drug treatment and parasite recovery was observed. These gametocytes later on would no longer extend their life in the RBC stage, unless mosquitoes bite the infected host. This phenomenon is similar to the case in human malaria infections treated with sulfadoxine-pyrimethamine (SP). Conclusions In this study, the antimalarial drug sulfadoxine induced gametocytogenesis in P. berghei, which could raise the risk factor for malaria transmission.